2021
DOI: 10.1186/s13244-021-01026-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical value of 3'-deoxy-3'-[18F]fluorothymidine-positron emission tomography for diagnosis, staging and assessing therapy response in lung cancer

Abstract: Lung cancer has the highest mortality rate of any tumour type. The main driver of lung tumour growth and development is uncontrolled cellular proliferation. Poor patient outcomes are partly the result of the limited range of effective anti-cancer therapies available and partly due to the limited accuracy of biomarkers to report on cell proliferation rates in patients. Accordingly, accurate methods of diagnosing, staging and assessing response to therapy are crucial to improve patient outcomes. One effective wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 50 publications
(122 reference statements)
0
8
0
Order By: Relevance
“…Further studies carried out between 2003 and 2016 have consistently reported that [ 18 F]-FLT (65) has a higher specificity but lower uptake when compared to 2-[ 18 F]-FDG (1). 182 This suggests that whilst less [ 18 F]-FLT (65) actually makes it into the cell, the likelihood of the tumour being malignant is higher if uptake occurs. [ 18 F]-FLT (65) therefore has an important role to play in the early diagnosis of malignant lesions, particularly if further structural modifications lead to improved cellular uptake.…”
Section: Pyrimidine Tracersmentioning
confidence: 99%
“…Further studies carried out between 2003 and 2016 have consistently reported that [ 18 F]-FLT (65) has a higher specificity but lower uptake when compared to 2-[ 18 F]-FDG (1). 182 This suggests that whilst less [ 18 F]-FLT (65) actually makes it into the cell, the likelihood of the tumour being malignant is higher if uptake occurs. [ 18 F]-FLT (65) therefore has an important role to play in the early diagnosis of malignant lesions, particularly if further structural modifications lead to improved cellular uptake.…”
Section: Pyrimidine Tracersmentioning
confidence: 99%
“…FLT is a thymidine analog that can be transported into cells and phosphorylated by thymidine kinase-1. Phosphorylated FLT cannot participate in subsequent deoxyribonucleic acid (DNA) synthesis and remains in cells due to the hydroxyl group at the 5′ end of the thymidine being replaced by 18 F. 105 Uptake of 18 F-FLT by tumor cells could reflect the rate of DNA synthesis and cell proliferation. 106 18 F-FLT PET/CT has been used for differentiation of benign and malignant tumors, assessment of treatment response, and prediction of prognosis in different malignancies.…”
Section: Ca-ix (Ca9)mentioning
confidence: 99%
“…The radiopharmaceutical 3′-deoxy-3′- 18 F-fluorothymidine ( 18 F-FLT), a thymidine analog used in positron emission tomography (PET) imaging, is a surrogate indicator of deoxyribonucleic acid synthesis [ 22 ]. 18 F-FLT PET is a valuable method for assessing hematopoietic proliferative activity in the bone marrow and extramedullary space [ 20 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%